2022
DOI: 10.3390/e24111688
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Habituation in Migraine Patients Based on High-Density EEG Analysis Using the Steady State of Visual Evoked Potential

Abstract: Migraine is a periodic disorder in which a patient experiences changes in the morphological and functional brain, leading to the abnormal processing of repeated external stimuli in the inter-ictal phase, known as the habituation deficit. This is a significant feature clinically of migraine in both two types with aura or without aura and plays an essential role in studying pathophysiological differences between these two groups. Several studies indicated that the reason for migraine aura is cortical spreading d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…People with migraines and visual symptoms (aura) show a greater decrease (about 9.8%) in brain wave coherence in response to visual stimuli compared to those without aura (about 8.9%). Previous studies in this field consistently highlight the differences between the two types of headaches, encompassing cortical coherence and habituation [14]. These investigations provide evidence supporting the involvement of CSD with a complex relationship and incomprehensible coherence in migraine.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…People with migraines and visual symptoms (aura) show a greater decrease (about 9.8%) in brain wave coherence in response to visual stimuli compared to those without aura (about 8.9%). Previous studies in this field consistently highlight the differences between the two types of headaches, encompassing cortical coherence and habituation [14]. These investigations provide evidence supporting the involvement of CSD with a complex relationship and incomprehensible coherence in migraine.…”
Section: Discussionsupporting
confidence: 70%
“…Studies on migraines show that certain stimuli can cause synchronized brain activity in visual areas. This suggests that sensory processing has changed, and there may be a link between migraine sufferers having frequent visual auras and their visual systems not working properly [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Admittedly, the habituation deficit in episodic migraineur patients has not been reproduced in some studies [49]. Several recent studies, however, using high-density EEG and multisensory stimulations have confirmed this abnormality of sensory processing in the migraine brain [50,51]. Moreover, the habituation deficit paradigm is able to capture changes induced by pharmacological and non-pharmacological migraine preventive therapies [17,52,53].…”
Section: Discussionmentioning
confidence: 99%